Prevalence of enterotoxigenicity in human and nonhuman isolates of Yersinia enterocolitica. - Pai, C H (1978)
A total of 414 cultures of Yersinia enterocolitica isolated from human and nonhuman sources were examined for heat-stable enterotoxin (ST) production to determine whether enterotoxigenicity was related to the source of isolation, serotype, or biochemical characteristics of the organism. A total of 65% of all cultures were found to produce ST. Enterotoxin production was much more prevalent in strains isolated from humans (218/232) than in those isolated from animals (17/34), water (9/49), raw milk (14/44), and food (10/55). Strains belonging to the serotypes O:3; 8; 5,27; 6,30; 9, often isolated from human infections, were almost always enterotoxigenic (191/196), although ST production was also highly prevalent among a few other serotypes. The most significant difference was observed between the groups that differed in the ability to ferment rhamnose; only 13 of 130 rhamnose-positive isolates produced ST (10%) compared to 255 of 284 rhamnose-negative cultures (90%). These results suggest that ST production is ubiquitous in Y. enterocolitica, with the highest prevalence among strains associated with human infections.